Serious Game for Caloric Burning in Morbidly Obese Children - Díaz Román, José David (Taylor & Francis Group, 2021)
A new report on childhood obesity is published every so often. The bad habits of food and the increasingly sedentary life of children in a border society has caused an alarming increase in the cases of children who are overweight or obese. Formerly it seemed a problem of countries with unhealthy eating habits, such as the United States or Mexico in Latin-America, where junk food is part of the diet during childhood. However, obesity is a problem that we already have around the corner and that is not so difficult to fight in children. In the present research, the development of an application that reduces the problem of the lack of movement regarding the children of a smart city is considered a future problem which It is the main contribution, coupled with achieving an innovative way of looking for an Olympic sport without the complexity of physically moving to a space with high maintenance costs and considering the adverse weather conditions. We use Unity to model each Avatar associated with a set of specific sports, such as Water polo, Handball, Rhythmic Gymnastics and others.